В полете к солнцу: стихи и поэмы : [перевод с удмуртского] / Кузебай Герд - Герд Кузебай (Удмуртия, 1989)
Экземпляры: ф.12 (20151124) / Инвентарный номер: 031403 / Цена: 1.10 / Авт.знак: Г 37 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6